Influence of Chemical Heterogeneity and Third Body on Adhesive Strength: Experiment and Simulation - Lyashenko, Iakov A.; Li, Qiang; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2021)
We investigate experimentally and numerically the influence of chemical heterogeneity and of third-body particles on adhesive contact. Chemical heterogeneity is generated by chemical treatment of the contacting bodies changing locally the surface energy. For studying the influence of the third body, two types of particles are used: sand particles with various geometrical shapes and sizes, and steel spheres of equal radius. Dependencies of the normal force on the indentation depth at both indenting and pull-off as well as the evolution of the contact configuration are investigated. Corresponding numerical simulations are carried out using the boundary element method (BEM).